Sensory Quality and Cooking Loss of Broiler Chicken Nuggets with the Addition of Yellow Corn - Septian, I Gede Nano; Baeti, Husnul; Fahrullah, Fahrullah; Yulianto, Wahid; Kisworo, Djoko (Faculty of Agriculture, Tompotika Luwuk University, 2025)
The term